Towards a comprehensive sustainable assessment of beef cattle systems: integrating bioeconomics and animal science - Kuhn, Joana Gasparotto; Durante Mühl, Diego; Costa, Cainã Lima; Allegretti , Gabriela; Oliveira, Letícia de; Talamini, Edson (Acta Scientiarum. Animal Sciences, 2024)
Studies with bioeconomic modeling can be identified in animal science. However, there are distinct typologies associated with the term bioeconomy with different meanings and approaches. The present study aims to examine the Bioeconomy/Bioeconomics approaches used in animal science research and discuss the implications and benefits of integrating these areas of knowledge. The method consisted of systematic literature review with quantitative and qualitative analyzes of the content of articles obtained from the Scopus® database. In the process of searching and analyzing the articles, we defined beef cattle as representative of animal science. Followed the PRISMA Protocol guidelines. The results confirmed that the use of the term bioeconomic has been recurrent in this field of knowledge since 1994. However, the approach given to the term refers mainly to studies combining animal performance (bio) and economic returns (economic) because of variables of interest, evident in the set of indicators reported in the articles analyzed. Despite the relevance of these studies, we discuss some implications and reasons for adopting other bioeconomy approaches in animal science. We conclude that the integration between Bioeconomics and animal science can significantly broaden the scope of analysis, the what relevant to the contemporary challenges of promoting sustainable production systems.